Synthesis of chiral pyrene-based 1,4-dithiins - Keck, Christoph; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2024)
The 1,4-dithiin motif is known for its reversible redox properties to generate radical cations and diradical dications and thus is interesting for organic electronic applications. However, examples where this motif is embedded into chiral larger fused aromatic compounds are very rare. Here we describe the syntheses of several structurally related pyrene fused dithiins and their spectroscopic investigations with a focus on tuning circular dichroism, with respect to the g values, depending on their connectivity.